ISLAMIC ACCOUNTING KNOWLEDGE: FRAMEWORK AND FUTURE RESEARCH - Wahyuni TD, Ika Sari (Journal of Business Studies and Management Review, 2025)
This paper aims to provide a comprehensive framework for understanding Islamic accounting knowledge and to outline future research directions in this field. Islamic accounting is a specialized area that integrates financial reporting with Islamic ethical principles, emphasizing transparency, fairness, and social responsibility. This study reviews existing literature to identify key components of Islamic accounting knowledge and proposes a structured framework to guide future research. The paper concludes with recommendations for future research, highlighting areas that require further exploration to enhance the development and application of Islamic accounting practices. This paper employs bibliometric analysis to examine past and contemporary research topics, selecting and appraising contributions while analysing and consolidating data. A methodical approach has been utilised to identify, assess, and incorporate pertinent Islamic accounting knowledge literature studies. After screening and analysing 126 selected documents with the VOS viewer, it is evident that among a thousand keywords, three stand out in terms of frequency and link strength. The research highlights the considerable academic interest in themes such as "Islamic," accounting," and "knowledge," underscoring their importance. The findings of this paper help bridge the gap in Islamic accounting knowledge by linking Western accounting methods with religious values. The theoretical significance of this paper lies in establishing a correlation among three key research domains: Islamic, Accounting, and Knowledge. The outcomes reflect fairness, justice, and transparency. This integration can potentially create Islamic accounting, a specialized field that integrates financial reporting with Islamic ethical principles, emphasizing transparency, fairness, and social responsibility based on Islamic principles.